2021
DOI: 10.1111/jac.12473
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of water status in field‐grown wheat using beta mixed regression modelling based on fast chlorophyll fluorescence transients: A method for drought tolerance estimation

Abstract: Wheat (Triticum aestivum L.) along with rice and maize belongs to the staple crops essential for feeding the world's population. It is cultivated on fields of a total area bigger than 220 million hectares (about 1.5% of earth land area) providing about 19% of food calories, the same as rice and fourfold more than maize. It has been estimatedthat the global wheat yield should increase by 2% yearly to satisfy food needs (FAO, 2014). Its production is strongly dependent on climatic conditions (Ahmadi & Baker, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We have focused on the fact of steady yield increase even in years of drought, and not on the reasons for yield decline. Independently, in a recent experiment, we analyzed changes in water saturation deficit in field‐grown wheat, during the hot and dry summers of 2017 and 2018 (Spyroglou et al., 2021), and we found that the Belissa, Bonanza, and Frisky winter wheat cultivars from the Polish crop‐seed market were tolerant to drought. Belissa is a Polish cultivar, selected by pedigree breeding, based on monitoring phenotypic traits (habit, health, quality traits, overwintering) to the F6 generation, followed by an assessment of features related to the yield potential and other economically valuable properties (Matysik et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We have focused on the fact of steady yield increase even in years of drought, and not on the reasons for yield decline. Independently, in a recent experiment, we analyzed changes in water saturation deficit in field‐grown wheat, during the hot and dry summers of 2017 and 2018 (Spyroglou et al., 2021), and we found that the Belissa, Bonanza, and Frisky winter wheat cultivars from the Polish crop‐seed market were tolerant to drought. Belissa is a Polish cultivar, selected by pedigree breeding, based on monitoring phenotypic traits (habit, health, quality traits, overwintering) to the F6 generation, followed by an assessment of features related to the yield potential and other economically valuable properties (Matysik et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All the JIP-test parameters can be divided into four groups in general: (1) basic measured and calculated values; (2) quantum yield and probabilities/efficiencies; (3) energy flux; (4) performance indices. Among them, the parameters used in this study are listed in detail in Table 1 (Spyroglou et al , 2021) with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, the parameters used in this study are listed in detail in Table 1 (Spyroglou et al, 2021) with minor modifications.…”
Section: A Brief Information Of Ojip Fluorescence Transient and Jip-testmentioning
confidence: 99%
“…The physiological response to stress is most often visualized by the rate of gas exchange and chlorophyll fluorescence parameters, which can be a useful tool to estimate the tolerance level of plants to various environmental factors. This approach has been used in the rapid assessment of drought tolerance of the field-grown wheat varieties [74], the analysis of dynamics of salinity stress in A. thaliana seedlings [75], and in the search for adaptation mechanisms to the cold springs in maize [76] as well as in the comparative analysis of the cold tolerance in two Miscanthus genotypes [30]. In our experiments, chilling treatment (10-12 • C) did not cause changes in net CO 2 assimilation (Figure 4A), the quantum yield of photosystem II (φ PSII ) (Figure 4B), or maximal photochemical efficiency of photosystem II (F v /F m ) (Figure 4C) in the M1 and M2 genotypes.…”
Section: (Micro)climatic Conditions Of Plantations Versus the Adaptab...mentioning
confidence: 99%